Posted by **Anonymous** on Sunday, March 11, 2012 at 11:42pm.

Prove the following:

[1+sinx]/[1+cscx]=tanx/secx

=[1+sinx]/[1+1/sinx]

=[1+sinx]/[(sinx+1)/sinx]

=[1+sinx]*[sinx/(sinx+1)]

=[sinx+sin^2x]/[sinx+1]

=[sinx+(1-cos^2x)]/[sinx+1]

=???

This is where I'm stuck. Can someone help me. Please check what I got is right so far it's possible that I made a mistake somewhere.

Please and Thank you

## Answer this Question

## Related Questions

- Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...
- Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...
- Mathematics - Trigonometric Identities - Prove: (tanx)(sinx) / (tanx) + (sinx...
- Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...
- drwls - My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an ...
- math - the problem is 2cos^2x + sinx-1=0 the directions are to "use an identity ...
- Precalculus/Trig - I can't seem to prove these trig identities and would really ...
- Mathematics - Trigonometric Identities - Prove: sinx + tanx = tanx (1 + cosx) ...
- Math - Im really struggling with these proving identities problems can somebody ...
- Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...